Pengetahuan, Persepsi dan Kebijakan Pengelolaan Ekowisata Gajah di Kawasan Aek Nauli, Danau Toba - Wanda Kuswanda (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2019)
The development of tourist destinations is very important to increase the return of traveler to Lake Toba, North Sumatra. The Aek Nauli Elephant Conservation Camp (ANECC) is one of the locations that being developed in the Special Purpose Forest Region (SPFR) of Aek Nauli as a location conservation and scientific tourism for Sumatran elephants. Elephant was chosen an 'icon' for new ecotourism because them are animals that attract communities. This study aims to obtain information about knowledge and visitor perceptions as well as policy recommendations to develop elephant scientific tourism for supporting the tourist visits to Lake Toba in ANECC, SPFR of Aek Nauli, North Sumatra. This research was conducted in the ANECC area for six months, starting from May to October 2018. Data collection were used by questionnaires and interviews. Respondents are ANECC visitors who were selected by using the purposive random sampling method. Data analysis is carried out quantitatively whit frequency tables. The results showed that visitors knowledge about the existence of elephant ecotourism came from friends and social media. They visited ANECC for curiosity and interest in the presence of elephants. Perception of 85% respondents is positive for elephant scientific tourism because of good service, elephant attractions presentation and adequate facilities and free. The policy references are recommended for the ANECC development as follows implement to animal welfare and health for elephants, reinforce coordination and communication between managers, develop cooperation with business society (travel and hotels), to make ecotourism packages that integrated with Lake Toba, improve promotion through internet marketing and social networking and collaborating with local communities.